Heroes of the environment : True stories o0f people who are helping to protect our planet - Rohmer, Harriet; McLaughlin, Julie (U.S.A. : Scholastic, 2009)
In every story, you're right alongside the heroes as they take on the problems, overcome obstacles, and find succes. These twelve heroes represent just a few of the manu people who are working today to protect the earth and all its residents. Their stories will inspire you, and you'll learn how you can support, join - and even lead - efforts to heal our environment and keep it clean and healthy for generations to come.
CONTENTS Introduction 1. Raising food in the city 2. Discovering a new way to clean polluted water 3. Turning waste into good business and good jobs 4. Bringing solar power to indian country 5. Speaking out to a big oil company 6. Inventing eco-machines 7. Recycling electronic waste 8. Saving west Virginia's oldest mountains 9. Fighting the enemies of the environment 10. Protecting the Lousiana wetlands 11. Saving the porcupine river caribou 12. Safeguarding the California coast How you can get involved Acknowledgments Photo credits
Incluye Contents
Keywords: ENGLISH LITERATURE; MEDIO AMBIENTE; ENVIRONMENT; ECOLOGÍA; ECOLOGY; SHORT STORIES